The challenge of achieving basal energy, iron and zinc provision for home consumption through family farming in the Andes: a comparison of coverage through contemporary production systems and selected agricultural interventions - Arce, A.; Creed-Kanashiro, Hilary M.; Scurrah, M.; Ccanto, Raul I.; Olivera, Edgar; Burra, Dharani Dhar; Haan, Stef de (Springer, 2016)
Background